Estimating the degree of body immunodepression in leukosis-infected cattle - Yu. P. Smirnov; I. L. Suvorova (Аграрная наука Евро-Северо-Востока, 2016)
The paper presents some results of surveys estimating of body immunodepression in leukosis-infected cattle depending on the total percentage of juvenile, stab and segmentated neutrophilic leukocytes in peripheral blood that are the first how protect body against infectious diseases and foreign invaders. If the value is 0 to 20%, immunodepression is estimated at high number of diseased and suspect animals - about 90.7% during 12 months. At total content of these cells about 21 to 30% - as lowered with 31.8% of diseased and suspect animals; at 31% and more - as low with 0.0. 2.5% of diseased and suspect animals. Dependency was revealed makes it possible to modulate the degree of sensitivity to the immunosuppressive effects of the BLV in susceptible animals. It is believed that various changes in the content of the neutrophils are evident in all malignant re-birth of marrowy and lymphoid tissues. Estimating the degree of body immunodepression in leukosis-infected cattle in asymptomatic stage of leukosis depending on the total percentage of neutrophilic leukocytes, identification of animals with the high degree of body immunodepression and their timely segregation will prevent the possible death and improve the effectiveness of control and eradication programs for BLV infection. In addition, it is possible to get meat products from these animals fit for food of man.